Testosterone boosts physical activity in male mice via dopaminergic pathways - Jardí, Ferran (Sci Rep, 2018)
Low testosterone (T) in men, especially its free fraction, has been associated with loss of energy. In accordance, orchidectomy (ORX) in rodents results in decreased physical activity. Still, the mechanisms through which T stimulates activity remain mostly obscure. Here, we studied voluntary wheel running behavior in three different mouse models of androgen deficiency: ORX, androgen receptor (AR) knock-out (ARKO) and sex hormone binding globulin (SHBG)-transgenic mice, a novel mouse model of “low free T”. Our results clearly show a fast and dramatic action of T stimulating wheel running, which is not explained by its action on muscle, as evidenced by neuromuscular studies and in a muscle-specific conditional ARKO mouse model. The action of T occurs via its free fraction, as shown by the results in SHBG-transgenic mice, and it implies both androgenic and estrogenic pathways. Both gene expression and functional studies indicate that T modulates the in vivo sensitivity to dopamine (DA) agonists. Furthermore, the restoration of wheel running by T is inhibited by treatment with DA antagonists. These findings reveal that the free fraction of T, both via AR and indirectly through aromatization into estrogens, stimulates physical activity behavior in male mice by acting on central DA pathways.